RESPON PERTUMBUHAN BIJI KECAPI (Sandoricum koetjape(Burm.f.)Merr) TERHADAP PEMBERIAN ZPT IBA DAN BAP SECARA IN VITRO - Abraham Budiatno Harry Nugroho; Eny Dwi Pujawati; Eva Prihatiningtyas (Jurnal Sylva Scienteae, 2020)
Kecapi (Sandoricum koetjape Merr Burm. f.) has many benefits and uses of which fruit can be eaten, and the wood can be used for furniture. Therefore, the researchers conducted a study with the method of tissue culture (in vitro) because the kecapi wood has potential as an alternative wood. This research was conducted in a tissue culture laboratoryof UPT Food Crops and Horticulture Council, Guntung Manggis, Banjarbaru, South Kalimantan. The treatment of the observed growth response i.e. explant for 8 weeks and the organ is formed from explant. We used a descriptive data analysis. The results showed that the formation of roots perfectly, occurred on treatment using the hormone combination of IBA and BAP with a concentration of 0.5 ppm; Formation of shoots perfectly, occurs in treatment uses a combination of hormone IBA and BAP with a concentration of 4 ppm; The formation of the callus, occurred on treatment using the hormone combination of IBA and BAP with a concentration of 0.5 ppm. So it can be inferred that the research response to the growth of the harp (Sandoricum koetjape Merr Burm. f.) against granting ZPT IBA and BAP in in vitro experiment based on all of the observation data obtained after 8 weeks there are 12 eksplan that make up the plant organs namely organogenesis and 1 eksplan that form the kalus. Most of the seeds of the harp that obtain treatment 0.5 ppm, 1 ppm, 2 ppm and 4 ppm only managed to reach the phase changes color to green and the addition of size or swell. The amount of esksplan nth response is present on the combination treatment ZPT IBA and BAP of 2 ppm.Keywords: Kecapi; In Vitro; Growth Response